Intrinsic and Extrinsic Motivation as Predictors of Academic English Reading Performance among Multidisciplinary University Students - Afdaleni, Afdaleni; Lubis, Fitriadi; Jasrial, Dedi; Yelfiza, Yelfiza (UNIB Press, 2025)
Numerous studies in the last decade have predominantly examined reading motivation among English major students, leaving limited evidence from multidisciplinary non-English majors in social sciences and humanities. This present study aims to examine the intrinsic and extrinsic motivation levels and their relationship with academic reading performance among 150 undergraduate students from five non-English majors at two private universities in Bukittinggi, Indonesia. This quantitative correlational research design collected the data through a reading motivation questionnaire comprising intrinsic and extrinsic dimensions, and an academic English reading test. The data were analyzed descriptively (mean and standard deviation) and inferentially using Pearson correlation analysis. The results revealed that students’ academic reading ability was at a moderate-to-high level (M = 78.4, SD = 7.6). Students have better academic reading performance in literal comprehension than in inferential and evaluative comprehension. Additionally, the statistical analysis results show that there is a significant correlation between students’ intrinsic motivation and their reading performance (r = 0.47, p < 0.001). In contrast, the correlation between students’ intrinsic motivation and reading performance was lower (r = 0.21, p. < 0.005). These findings suggest that the most influential factor to foster students’ ability in academic reading was intrinsic motivation.